Pengaruh Lingkungan Kerja, Keselamatan Dan Kesehatan Kerja (k3) Terhadap Kinerja Karyawan PT. Resqtec Indonesia Di Ruas Tol Kayuagung – Palembang - Nugraha, Bintang; Syahrinullah, Syahrinullah (Pascasarjana Universitas Muhammadiyah Mamuju, 2024)
This study examines the influence of the work environment, safety, and occupational health on employee performance at PT Resqtec Indonesia, Kayuagung - Palembang Toll Road. The creation of a conducive work environment, the guarantee of safety, and the maintenance of health are significant factors in the enhancement of employee performance. A descriptive qualitative research method was employed to gain an in-depth understanding of the subject matter through interviews with company employees. The findings indicated that an adequate work environment exerts a beneficial influence on employee performance. However, certain impediments, such as inadequate lighting, can negatively impact employee performance, particularly in the context of responding to accidents in the field. Furthermore, occupational safety and health play an important role, with regular monitoring of employees' physical and mental health being required. The results of this study demonstrate that in the work environment, safety, and occupational health have a positive and significant influence on the performance of employees of PT Resqtec Indonesia. It is therefore recommended that the company implement improvements to portable lighting for more flexible field situations, as well as conduct regular medical check-ups and psychological tests to ensure and monitor the physical and mental health of employees.